Low thoracic skeletal mass index, a novel marker to predict recurrence of aspiration pneumonia in the elderly stroke patients. - Bo Mi Gil; Sun Im; Yu Jin Hong; Hye Seon Kang (PLoS ONE)
Purpose We investigated whether thoracic skeletal muscle mass index at the diagnosis of aspiration pneumonia (AP) is a predictor for AP recurrence and explored predicting factors for AP recurrence in patients with stroke. Patients and methods This study retrospectively reviewed data of patients with AP who were diagnosed with stroke and who had full medical follow-up data from January 2014 to July 2020 in the Catholic University of Korea Bucheon St. Mary's Hospital. AP was defined based on clinical signs and/or symptoms suggestive of pneumonia and radiologic findings of pneumonic infiltrations in the dependent portions of the lung. We measured thoracic muscle volume using the cross-sectional area (CSA) of the erector spinae muscle (ESMCSA, cm2) at the 12th vertebral region. Computed tomography scans at the time of AP diagnosis during the acute stroke period were used for analysis and respective CSAs were divided by height squared (m2) to yield the muscle index at T12 (T12MI, cm2/m2) to normalize for stature. Multivariate logistic regression models were used to investigate relationships between clinical parameters and AP recurrence. Results During the study period, a total of 268 stroke patients with dysphagia who developed AP were analyzed. The mean T12MI of patients with and without recurrence of AP was 622.3±184.1 cm2/m2 and 708.1±229.9 cm2/m2, respectively (P = 0.001). Multivariate logistic regression revealed that lower T12MI (P = 0.038) and older age (P = 0.007) were independent predictors of AP recurrence in patients with stroke and dysphagia. Conclusion Low thoracic muscle index at the diagnosis of initial AP after stroke can predict subsequence AP recurrence.